2019
DOI: 10.1002/ppul.24270
|View full text |Cite
|
Sign up to set email alerts
|

Fractional exhaled nitric oxide in preterm‐born subjects: A systematic review and meta‐analysis

Abstract: Background Decreased lung function is common in preterm‐born survivors. Increased fractional exhaled nitric oxide (FeNO) appears to be a reliable test for eosinophillic airway inflammation especially in asthma. We, systematically, reviewed the literature to compare FeNO levels in preterm‐born children and adults who did or did not have chronic lung disease of prematurity (CLD) in infancy with term‐born controls. Methods We searched eight databases up to February 2018. Studies comparing FeNO levels in preterm‐b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 38 publications
3
32
0
Order By: Relevance
“…Diminished lung volume has been associated with more frequent wheezing illnesses, independent of atopic status . Indeed, normal levels of exhaled NO in former preterm proposed an alternative mechanism to eosinophilic inflammation for symptoms of wheezing and airway obstruction …”
Section: Discussionmentioning
confidence: 99%
“…Diminished lung volume has been associated with more frequent wheezing illnesses, independent of atopic status . Indeed, normal levels of exhaled NO in former preterm proposed an alternative mechanism to eosinophilic inflammation for symptoms of wheezing and airway obstruction …”
Section: Discussionmentioning
confidence: 99%
“…These findings might suggest that lung diffusing capacity is not induced by eosinophil airways inflammation and that airways inflammation is different in ex-preterm children compared to asthmatics children. A recent meta-analysis with 640 preterms and 4,005 term controls found no difference in FeNO levels between ex-preterm and term subjects and between ex-preterm subjects with and without Chronic Lung Disease ( 36 ). To date, several studies have shown no eosinophilic markers in ex preterm children ( 35 , 37 ) suggesting an alternative inflammation pattern underlying wheezing and airway obstruction in ex-preterms subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Higher exhaled nitric oxide (eNO) levels are commonly found in people with an eosinophilic asthma phenotype 46 . However, a meta‐analysis of studies that measured eNO levels in preterm children with and without chronic lung disease found similar eNO levels as found in term controls 47 . These findings indicate that the etiology of airflow obstruction in preterm individuals with PPRD is likely different from individuals with eosinophilic asthma phenotypes.…”
Section: Small Airway Diseasementioning
confidence: 99%